Introduction to currency risk - Coyle, Brian (Chicago : Glenlake, New York : AMACOM, 2000)
"This introduction to the Currency Risk series of books explains the nature of risk, how it is measured and the short and long-term implications for business. It examines the concept of a broad policy towards currency risk management and in particular whether a business should seek to limit or hedge its exposure. A description is given of transaction, translation and economic exposure and methods for quantifying with a view to establishing a risk management strategy."--BOOK JACKET.
1. Financial Risk -- 2. Currency Risk -- 3. Transaction Exposures -- 4. Translation Exposures -- 5. Economic Exposures -- 6. Gains and Losses from Exposures -- 7. Identifying and Quantifying Exposures -- 8. Risk Management Strategies.
Includes index.
Keywords: Foreign exchange